2018
DOI: 10.1021/acs.jafc.7b05885
|View full text |Cite
|
Sign up to set email alerts
|

Several Pesticides Influence the Nutritional Content of Sweet Corn

Abstract: Herbicides are pesticides used to eradicate unwanted plants in both crop and non-crop environments. These chemistries are toxic to weeds due to inhibition of key enzymes or disruption of essential biochemical processes required for weedy plants to survive. Crops can survive systemic herbicidal applications through various forms of detoxification, including metabolism that can be enhanced by safeners. Field studies were conducted near Louisville, Tennessee and Painter, Virginia to determine how the herbicides m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…(2009) reported a significant increase in the content of carotenoids in a moderately sensitive sweet maize genotype. An increasing trend in the content of carotenoids after applying certain herbicides was also reported by Cutulle et al, (2018). The significant increase in the content of carotenoids in the sweet maize kernel could probably be explained by the formation of a large carotenoid pool as a result of mesotrione application (Kopsell et al, 2009).…”
Section: Accepted Manuscriptsupporting
confidence: 52%
See 2 more Smart Citations
“…(2009) reported a significant increase in the content of carotenoids in a moderately sensitive sweet maize genotype. An increasing trend in the content of carotenoids after applying certain herbicides was also reported by Cutulle et al, (2018). The significant increase in the content of carotenoids in the sweet maize kernel could probably be explained by the formation of a large carotenoid pool as a result of mesotrione application (Kopsell et al, 2009).…”
Section: Accepted Manuscriptsupporting
confidence: 52%
“…The markedly different trend in the content of phytochemicals obtained in this study might indicate the variability in their susceptibility to herbicides and also the dependence on the genotype. The obtained variations in the content of phytochemicals indicate there is an alteration in the plant biochemical pathway in the presence of herbicides and foliar fertilizer and emphasize the complexity of the metabolic pathway that occurs (Cutulle et al, 2018). The performed PCA revealed that the variation in the content of phytochemicals depended both on the genotype and the applied treatments.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
See 1 more Smart Citation
“…However, they found a 1.2 kg ha −1 glyphosate dose slightly reduced the yield of GR maize, even though a sequential treatment of 0.96 plus 0.72 kg ha −1 glyphosate had no effect on yield. Mild stress caused by the maize herbicides mesotrione, topramezone, and nicosulfuron was reported to increase Mg, Fe, and Mn in leaves of non-transgenic maize (Cutulle et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Sweet maize (Zea mays L.) is extensively planted in China and many other regions of the world due to the fact of its high sugar content and better flavor [6][7][8][9]. China has become the country with the second largest area of growing sweet maize since 2008 [10].…”
Section: Introductionmentioning
confidence: 99%